Forest fires in Ulvinsalo strict nature reserve in Northern Finland - Haapanen, Antti; Siitonen, Pertti (Silva Fennica, 1978)
The study is the first report of a larger project concerning fire ecology in the Finnish boreal forests. Modern forestry has never been practiced in the Ulvinsalo strict nature reserve (2,500 ha) in Northern Finland in the county of Kuhmo. Forest fires have been uncommon because of mosaic of mineral and peat soils. The forests are mostly Norway spruce ( (L.) H. Karst.) dominated with Scots pine ( L.) often as the oldest trees of a stand. Forest fires were dated by counting annual rings from cambium to the fire scar in pines. 73 stands covering 1,207 ha were surveyed, over 80% of which was on mineral soil.Picea abiesPinus sylvestris